Gastrointestinal endoscopy's carbon footprint - Su Bee Park; Jae Myung Cha (Korean Society of Gastrointestinal Endoscopy, 2023)
Climate change is a global emergency. Consequently, current global targets to combat the climate crisis include reaching net-zero carbon emissions by 2050 and keeping global temperature increases below 1.5 ˚C. In 2014, the healthcare carbon footprint was 5.5% of the total national footprint. Gastrointestinal endoscopy (GIE) has a large carbon footprint compared to other procedures performed in healthcare facilities. GIE was identified as the third largest generator of medical waste in healthcare facilities for the following reasons: (1) GIE is associated with high case volumes, (2) GIE patients and relatives travel frequently, (3) GIE involves the use of many nonrenewable wastes, (4) single-use devices are used during GIE, and (5) GIE is frequently reprocessed. Immediate actions to reduce the environmental impact of GIE include: (1) adhering to guidelines, (2) implementing audit strategies to determine the appropriateness of GIE, (3) avoiding unnecessary procedures, (4) using medication rationally, (4) digitalization, (5) telemedicine, (6) critical pathways, (7) outpatient procedures, (8) adequate waste management, and (9) minimizing single-use devices. In addition, sustainable infrastructure for endoscopy units, using renewable energy, and 3R (reduce, reuse, and recycle) programs are necessary to reduce the impact of GIE on the climate crisis. Consequently, healthcare providers need to work together to achieve a more sustainable future. Therefore, strategies must be implemented to achieve net-zero carbon emissions in the healthcare field, especially from GIE, by 2050.